Review of Areti Adamopoulou, Τέχνη και ψυχροπολεμική διπλωματία: Διεθνείς εικαστικές εκθέσεις στην Αθήνα (1950–1967): [Art and Cold War diplomacy: International art exhibitions in Athens, 1950–1967] - Teneketzis, Alexandros (Historein, 2023)
Review of Areti Adamopoulou, Τέχνη και ψυχροπολεμική διπλωματία: Διεθνείς εικαστικές εκθέσεις στην Αθήνα (1950–1967) [Art and Cold War diplomacy: International art exhibitions in Athens, 1950–1967]. Thessaloniki: University Studio Press, 2019. 422 pp.